2019
DOI: 10.3389/fncel.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of Adult Zebrafish Oligodendrocyte Progenitor Cells

Abstract: Low remyelination efficiency after spinal cord injury (SCI) is a major restraint to successful axonal and functional regeneration in mammals. In contrast, adult zebrafish can: (i) regenerate oligodendrocytes and myelin sheaths within 2 weeks post lesion; (ii) re-grow axonal projections across the lesion site and (iii) recover locomotor function within 6 weeks after spinal cord transection. However, little is known about the intrinsic properties of oligodendrocyte progenitor cells (OPCs), the remyelinating cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…OPCs show no response to depolarization in the first wave of OPC proliferation in embryonic development in the forebrain, with responses not observed in OPCs until P5 ( Ziskin et al, 2007 ), although there are responses to depolarization in the spinal cord, see Osterstock et al (2018) . However, exposure to glutamate induces mEPSCs in OPCs both in very early postnatal development and into maturity in the forebrain and spinal cord, ( De Biase et al, 2010 ; Spitzer et al, 2019 ; Tsata et al, 2019 ), and in both gray ( Bergles and Jahr, 2000 ; Mangin et al, 2008 ), and white matter ( Kukley et al, 2007 ; Ziskin et al, 2007 ; Káradóttir et al, 2008 ; Etxeberria et al, 2010 ). The degree of response to glutamate differs greatly between OPCs, pre-OLs, and OLs.…”
Section: Direct Synaptic Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPCs show no response to depolarization in the first wave of OPC proliferation in embryonic development in the forebrain, with responses not observed in OPCs until P5 ( Ziskin et al, 2007 ), although there are responses to depolarization in the spinal cord, see Osterstock et al (2018) . However, exposure to glutamate induces mEPSCs in OPCs both in very early postnatal development and into maturity in the forebrain and spinal cord, ( De Biase et al, 2010 ; Spitzer et al, 2019 ; Tsata et al, 2019 ), and in both gray ( Bergles and Jahr, 2000 ; Mangin et al, 2008 ), and white matter ( Kukley et al, 2007 ; Ziskin et al, 2007 ; Káradóttir et al, 2008 ; Etxeberria et al, 2010 ). The degree of response to glutamate differs greatly between OPCs, pre-OLs, and OLs.…”
Section: Direct Synaptic Transmissionmentioning
confidence: 99%
“…For example, adult zebrafish, unlike mammals, are capable of regenerating OLs and remyelinate axons within 2 weeks of lesion. This indicates that zebrafish glia could be a useful model for mammalian remyelination after injury or disease ( Tsata et al, 2019 ). The basic channel properties and expression in zebrafish OPCs were similar to mammalian OPCS, which opens up the possibility that determining how OPCs differently respond in this model could aid our understanding of remyelination in mammals.…”
Section: Disease and Treatmentmentioning
confidence: 99%
“…3C) supports their generation from RG in the adult zebrafish brain. In addition, flow cytometry of double transgenic fish that combine the RG-specific her4.1:mCherry reporter with the OPC-specific reporter olig2:gfp (Shin et al, 2003;Kroehne et al, 2017;Tsata et al, 2019) [Tg(her4.1:mcherry; olig2:gfp)] revealed that 28.6±3.9% of all olig2:GFP cells were mCherry low /GFP high double positive ( Fig. S4B,C).…”
Section: Lineage Tracing Of Radial Glia-derived Newborn Neurons In Thmentioning
confidence: 99%
“…Beyond developmental tiling, OPCs remain evenly tiled throughout life and utilize similar processes of migration, proliferation, contact-mediated repulsion, and apoptosis to maintain their spacing ( Hughes et al 2013 ; Tsata et al 2019 ). While a number of chemotactic molecules have been investigated in developmental OPC tiling, adult tiling and how it is maintained remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%